Negotiating Autonomy and Identity: A Feminist Comparison of Female Protagonists in Runaway Bride And 27 Dresses - Muhammad Arief Budiman; Hetty Catur Ellyawati (Jolly Journal of English Education, 2025)
This study aimed to examine how women are represented in popular romantic comedy films by analyzing the portrayal of female agency and gender roles in Runaway Bride and 27 Dresses. Grounded in feminist film theory, the research seeks to understand how the female protagonists negotiate personal autonomy, romantic expectations, and societal pressures within patriarchal cultural contexts. Employing a qualitative textual analysis, the study systematically analyzed key scenes, character development, dialogue, and narrative structures in both films to identify recurring themes related to femininity, independence, and conformity to traditional gender norms. The findings indicated that while both films depict women striving for self-fulfillment and independence, their narratives simultaneously reinforced and challenging dominant gender ideologies. These ambivalent representations reflected broader socio-cultural discourses on contemporary femininity and empowerment. The study concluded that romantic comedies occupy a complex position in mediating feminist ideals, reproducing conventional gender expectations while offering limited spaces for female agency. By highlighting these contradictions, the research contributed to feminist media studies and emphasizes the importance of critical media literacy in interpreting gender representation in mainstream cinema.